Multi-Echelon vs. Single-Echelon Inventory Control Policies for Low-Demand Items - Hausman, Warren H.; Erkip, Nesim K. (Management Science, 1994)
Multi-echelon inventory systems are often controlled as a network of single-echelon inventory systems for simplicity of managerial authority, organizational control, and performance monitoring. This paper explores the amount of suboptimization in such a situation, using an actual demand data set provided by other researchers. We consider low-demand, high-cost items controlled on an (S − 1, S) basis, with all warehouse stockouts met on an emergency-ordering basis. We demonstrate that the suboptimality penalty for this data set is 3% to 5% when single-echelon systems are appropriately parameterized.